PROPOLIS EXTRACTS FROM SOUTHERN SERBIA OBTAINED BY VARIOUS EXTRACTION TECHNIQUES - Vasić, Marijana; Rajković, Katarina; Simić, Valentina (ACADEMIC REVIEW, 2019)
The main goal was to define the influence of the extraction technique on the yield and total phenolics content in propolis extracts from South Serbia. There has been presented a comparison of the effectiveness of three propolis extraction techniques: Maceration, Heat reflux extraction and Ultrasound-assisted extraction with respect to yield and total phenolics content in propolis extracts. The extracts obtained by the Heat reflux extraction contained higher amounts of extractive substances as well as phenolic compounds than those obtained by Мaceration and Ultrasound-assisted extraction.